Students’ interests and attitudes toward science, technology, engineering, and mathematics careers - Arifin Septiyanto; Dwi Oetomo; Nurma Yunita Indriyanti (Institute of Advanced Engineering and Science, 2024)
Science, technology, engineering, and mathematics (STEM) education teaches students critical thinking skills that they can use to solve problems even after they enter the workforce. This study aimed to i) determine student attitudes toward the STEM field in each school area; ii) determine student interest in the STEM field in each school area; and iii) determine the correlation between student attitudes toward the STEM field and school area and student interest in STEM. This was a quantitative study with a cross-sectional survey design. The sample for this study came from Boyolali Regency in Central Java, Indonesia, and was divided into three groups: rural schools (24%), suburban schools (36.2%), and urban schools (39%). The proportional stratified random sampling technique was used to select the research sample of students in grades 7–9. The Spearman Rank technique was used for data analysis. The results showed that there is a strong relationship between students’ attitudes toward STEM, school area, and interest in STEM careers. On the other hand, there is a weak correlation between students’ attitudes toward STEM, the school environment, and their interest in STEM careers.